Knowledge, attitudes and metabolic control of diabetic and cardiac patients - Bruna Emy Ono; Carolina Rodrigues Mendes Nogueira Cobra; Claudia Castelo Branco de Castro; Elisabete Sabetta Margarido; Rita de Cassia Gengo e Silva (Universidade Federal do Ceará, 2016)
Objective: to verify the relationship between knowledge, attitudes and metabolic control in diabetic and cardiac patients. Methods: descriptive, exploratory and cross-sectional study exploring the knowledge, attitudes and diabetes metabolic control in 46 participants with heart disease. Results: participants were predominantly male with incomplete secondary education who demonstrated poor knowledge and unfavorable attitudes towards the disease. There was no difference between participants with and without knowledge on variables of metabolic and clinical control of diabetes, neither with respect to attitudes towards the disease. Conclusion: knowledge about diabetes was unsatisfactory in patients with heart disease and unrelated to favorable actions and better disease control.